(untitled) (Conference on English Language Teaching, 2025)
This study examines the effectiveness of the Quora platform in enhancing English vocabulary and writing skills. Utilizing a systematic literature review methodology, it explores students’ perspectives on Quora’s educational impact. Findings indicate that Quora fosters vocabulary development, improves writing proficiency, and enhances critical thinking through interactive, authentic learning experiences. Its algorithm, designed to tailor content to user interests, promotes engagement and independent learning. The study underscores Quora’s potential as a transformative educational tool, recommending its integration into classroom activities to optimize students’ language acquisition.